SINERGITAS GURU DAN ORANG TUA DALAM MENUMBUHKAN KARAKTER POSITIF ANAK PENDIDIKAN ANAK USIA DINI ASSALAAM KOTA BENGKULU - Femi Imelia Utami (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2026)
The purpose of this study is to explain how teachers and parents collaborate to foster positive character in children at Assalaam Early Childhood Education Center in Bengkulu City, as well as to identify supporting factors and barriers. This is because character education during the golden age cannot be successful if it relies solely on one party. Five informants one school principal, one teacher, and three parents were selected using a descriptive qualitative approach through participant observation, documentation, and semi-structured interviews. The data were then analyzed using the Miles and Huberman interactive model. The research results revealed three main patterns of synergy at PAUD Assalaam: formal communication through monthly and semester evaluation meetings, daily informal communication after school, and technology-based communication via a WhatsApp group. Together, these form a character education ecosystem that harmonizes school and home environments in line with the concept of overlapping spheres of influence (Epstein); supporting factors include role awareness, technology utilization, and commitment.